RECOGNITION RADIO ECHO BIRDS ON THE BASIS OF RADAR MRL-5 - L. A. Dinevich (Наука. Инновации. Технологии, 2022)
The article describes computerized radar ornithological system, created on the basis of weather radar MRL-5, allowing automatically to conduct monitoring of bird migration at any time of day. The possibility of MRL-5 to obtain simultaneously ornithological and meteorological information allows you to build a combined radar maps, weather conditions with vector fields birds pass them to the operational use of the services of air traffic control. The proposed system is applied in Israel in the study of birds migration processes and the safety of aircraft in ornithological complex and meteorological conditions.